A conserved ClpP‐like protease involved in spore outgrowth in Bacillus subtilis. Issue 1 (19th August 2013) - Traag, Bjorn A.; Pugliese, Antonia; Setlow, Barbara; Setlow, Peter; Losick, Richard
Summary Germination and outgrowth of endospores of the Gram‐positive bacterium Bacillus subtilis involves the degradation and conversion to free amino acids of abundant proteins located in the spore core known as small acid‐soluble proteins (SASP). This degradation is mediated primarily by the germination protease Gpr. Here we show that YmfB, a distant homologue of ClpP serine proteases that is highly conserved among endospore‐forming bacteria, contributes to SASP degradation but that its function is normally masked by Gpr. Spores from a ymfB gpr double mutant were more delayed in spore outgrowth and more impaired in SASP degradation than were spores from a gpr single mutant. The activity of YmfB relied on three putative active‐site residues as well as on the product of a small gene ylzJ located immediately downstream of, and overlapping with, ymfB. We propose that YmfB is an orphan ClpP protease that is dedicated to the degradation of a specialized family of small protein substrates.